2009
DOI: 10.1159/000204760
|View full text |Cite
|
Sign up to set email alerts
|

Distal Left Main Coronary Bifurcation Lesions Predict Worse Outcome in Patients Undergoing Percutaneous Implantation of Drug-Eluting Stents: Results from the Drug-Eluting Stent for the Treatment of Left Main Disease (DISTAL) Study

Abstract: Objectives: We investigated the clinical outcome of stenting of unprotected left main coronary artery (LMCA). Methods: We studied 164 patients with nonbifurcated LMCA lesions (group A) and 96 patients with distal bifurcated lesions (group B). Results: Clinical follow-up was available in 100%. Angiographic follow-up was 87.3% in group A and 86% in group B (p = 0.922). There were significant differences in major adverse cardiac events at 1 (p = 0.014) and 2 years (p = 0.002) between group B (19.8%, 25.0%) and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…33,34 Unlike the conflicting results on the association of LM distal bifurcation lesions with MACE, a positive correlation between LM distal bifurcation presence and TVR after stenting has been consistently reported, a finding confirmed in this study. 13,15,24,26,35 Advanced age showed a negative correlation with TVR in the PCI group, confirming earlier results showing that older patients were less likely than younger patients to undergo coronary reintervention. 36 This may be because of the higher rates of death and supportive care and the lower incidence of symptoms because of minimal workload in older patients.…”
Section: Repeat Revascularizationsupporting
confidence: 86%
See 1 more Smart Citation
“…33,34 Unlike the conflicting results on the association of LM distal bifurcation lesions with MACE, a positive correlation between LM distal bifurcation presence and TVR after stenting has been consistently reported, a finding confirmed in this study. 13,15,24,26,35 Advanced age showed a negative correlation with TVR in the PCI group, confirming earlier results showing that older patients were less likely than younger patients to undergo coronary reintervention. 36 This may be because of the higher rates of death and supportive care and the lower incidence of symptoms because of minimal workload in older patients.…”
Section: Repeat Revascularizationsupporting
confidence: 86%
“…According to the report of Valgimigli et al, 25 percutaneous treatment was found to be a major predictor of poor long-term outcome in patients with LM distal disease; the difference was primarily attributable to differences in TVR rate. Furthermore, the recent report of Chen et al 26 concluded that the rates of death were similar between patients with LM distal bifurcation and those with nonbifurcation lesions but that the incidence of MACE was significantly higher in patients with LM distal bifurcation lesions, mainly because of a higher incidence of TVR. In fact, another report showed that the location of the lesion in LM stenosis did not influence mortality or MACE after LMCA stenting.…”
Section: All-cause Mortalitymentioning
confidence: 95%
“…29 In the subgroup of patients with ULM disease, MACCE was similar for patients with Figure 1). Observational data has demonstrated worse outcomes for patients undergoing PCI for distal ULM disease, 34,35 and patients with higher SYNTAX scores are more likely to have distal bifurcation involvement.…”
Section: Selective Use Of Percutaneous Coronary Intervention -Anatomimentioning
confidence: 99%
“…14,15 Provisional T-stenting technique has been preferred as default strategy in managing simple bifurcation lesions. 12 PCI of complex true bifurcation or whole bifurcation (Medina classification 1,1,1 or 0,1,1 16 demonstrated that a two-stent approach, followed by adequate final balloon inflation, may ensure continuous stent coverage of the SB ostium and decrease the stent malapposition rate, which are responsible for the restenosis and stent thrombosis events.…”
mentioning
confidence: 99%